Predicting Israeli Public Support for Capital Punishment: Crime Type and Severity, Offender, Observer, and Victim Characteristics - Cohen-Louck, Keren (Crime & delinquency, 2025)
This study investigates whether crime type and severity, as well as offender, observer, and victim characteristics predict public attitudes towards capital punishment in Israel. We surveyed Israeli citizens by phone. A random and representative sample of 594 participants, ages 20 to 74, read scenarios illustrating crimes and were asked about their perception of capital punishment as an appropriate punishment. The results indicate that most participants did not support capital punishment. Perceived high-crime severity, a crime that constitutes terrorism, and male observer (participant) status predicted 34% in an increased likelihood of supporting capital punishment. The discussion attributes the stronger support of capital punishment in cases of terrorism to the Israeli experience of chronic terrorism and explains gender differences by gender-role socialization.